KEPEMIMPINAN STRATEGIS: PEMIMPIN VISIONER, PENGEMBANGAN KAPASITAS SUMBER DAYA DAN ORGANISASI ADAPTIF - Gani, Nur Asni; Maulianza, Medo (Taksasila Edukasi Insani, 2024)
This study concerns with the implementation of National Health Insurance program, which was started on January 1 of 2014, which has caused changes in health area, especially among hospitals. The information regarding the senses, roles, and leadership model of the hospitals was acquired by conducting in-depth interviews with twelve informants from three hospitals in Tangerang City. This qualitative study incorporates the intersubjective phenomenology with IPA (Interpretative Phenomenology Analysis) approach.The analysis resulted in three propositions. First, strategic leadership is a condition where the leader has a broad vision with abilities in mitigating the future, managing risks, and creating excellent products within appropriate health services. Second, strategic leaders in the National Health Insurance era are instrumental in developing the resource capacity by creating commitments toward improvements of human resource competence and appreciation for higher work motivation. Third, the leaders guide the organization to adapt by making changes in the organizational structure and culture and controlling the implementation of the National Health Insurance through the utilization of technology. This strategic leadership is characterized by the presence of visionary leaders, the development of resource capacity, and the development of adaptive technology. This study produces a research model that can be applied not only in health industry but also in other industries by conducting quantitative assessments on the propositions discovered in this research.Keywords : strategic leadership, hospital, National Health Insurance